2019
DOI: 10.22605/rrh4717
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing health profession students’ willingness to practice in rural regions of Bosnia and Herzegovina: a cross-sectional study

Abstract: Introduction:The literature indicates different factors influencing recruitment of health professional students to work in rural areas. The purpose of this study is to explore the willingness of health profession students in the Faculty of Medicine Foca, University of East Sarajevo, Bosnia and Herzegovina to work in a rural area following graduation and the factors influencing incentives to pursue a rural career. Methods:The cross-sectional study included first-year through sixth-year students aged 18 years or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This fact suggests that it is necessary to improve social and emotional skills. By searching and analyzing systematic reviews and meta-analyzes from three databases (Pubmed/Medline, EM-BASE, Scopus) where the works were obtained in which a larger number of examinees were included, it was concluded that by implementing social and emotional learning programs nurses could acquire the knowledge, attitudes and skills necessary for understanding and managing emotions, achieving positive goals, maintaining positive relationships and making responsible decisions in work [34,35,36,37].…”
Section: Components Of Emotional Intelligence In Nursing Practicementioning
confidence: 99%
“…This fact suggests that it is necessary to improve social and emotional skills. By searching and analyzing systematic reviews and meta-analyzes from three databases (Pubmed/Medline, EM-BASE, Scopus) where the works were obtained in which a larger number of examinees were included, it was concluded that by implementing social and emotional learning programs nurses could acquire the knowledge, attitudes and skills necessary for understanding and managing emotions, achieving positive goals, maintaining positive relationships and making responsible decisions in work [34,35,36,37].…”
Section: Components Of Emotional Intelligence In Nursing Practicementioning
confidence: 99%
“…In this context, it is also necessary to underline that the cost or tuition of dental school has increased significantly, leading to potential student debt that must be financed largely by private loans for costs sometimes exceeding USD 25,000/year. The keenness of health profession courses for students to work in the countryside after graduation was reported [45]. It is also worth noting that female students and students who come from a rural community are also more inclined to opt for a career in rural areas [46].…”
Section: Influence and Motives On The Choice Of Professionmentioning
confidence: 99%
“…It is a must to reduce bureaucracy and increase the timeliness of treatment and care. Measures to improve access to health and social care systems for pre-frail and frail patients, as well as their caregivers, must be considered [25]. Also, CH is beneficial for patients with chronic conditions as well as for the frail, by improving access to health care services and allowing them to be monitored at home [26].…”
Section: Theoretical Basismentioning
confidence: 99%